2015
DOI: 10.1002/jcp.24897
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of molecular pathways mediating electric field-directed schwann cell migration by RNA-seq

Abstract: In peripheral nervous systems, Schwann cells wrap around axons of motor and sensory neurons to form the myelin sheath. Following spinal cord injury, Schwann cells regenerate and migrate to the lesion and are involved in the spinal cord regeneration process. Transplantation of Schwann cells into injured neural tissue results in enhanced spinal axonal regeneration. Effective directional migration of Schwann cells is critical in the neural regeneration process. In this study, we report that Schwann cells migrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 61 publications
0
26
0
Order By: Relevance
“…GCF_000002985.6]) by Bowtie2 (Langmead and Salzberg 2012), and differentially expressed genes were analyzed using the edgeR method (Robinson et al 2010) by the CLRNASeq program (ChunLab, Inc.). Genes with significant changes in expression (P < 0.05, fold change >1.2) (Yao et al 2015) were further analyzed, and genes whose FPKM (fragments per kilobase of transcript per million fragments) was zero were excluded. Scatter plot (Riedel et al 2013) and heat map analyses (Ewald et al 2015) were performed as previously described.…”
Section: Locomotion Assaysmentioning
confidence: 99%
“…GCF_000002985.6]) by Bowtie2 (Langmead and Salzberg 2012), and differentially expressed genes were analyzed using the edgeR method (Robinson et al 2010) by the CLRNASeq program (ChunLab, Inc.). Genes with significant changes in expression (P < 0.05, fold change >1.2) (Yao et al 2015) were further analyzed, and genes whose FPKM (fragments per kilobase of transcript per million fragments) was zero were excluded. Scatter plot (Riedel et al 2013) and heat map analyses (Ewald et al 2015) were performed as previously described.…”
Section: Locomotion Assaysmentioning
confidence: 99%
“…The effect of EFs on cell migration has been reported in a number of investigations. In previous studies, we found that both SCs 18 and OPCs migrated toward the anodal pole of an applied EF 19 . The increase of directedness of anodal migration of these cells is in proportion to the strength of the applied EF (50 to 200 mV/mm).…”
Section: Introductionmentioning
confidence: 71%
“…Signal transduction is involved in the assembly and disassembly of the protein complex thereby controlling cell motility and migration direction. In previous publications, we have reported that the migration of SCs and OPCs can be directed by an applied electric field, and we performed RNA-seq to explore the pathways that regulated the cell migration for each type 18,19 . In this study, we jointly analyzed the RNA-seq data for OPCs and SCs subjected to EFs and then identified significantly enriched GO terms associated with DEGs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations